Prognostic Role of Lymph Node Positivity and Number of Lymph Nodes Needed for Accurately Staging Small-Bowel Neuroendocrine Tumors - Zaidi, Mohammad Y; Lopez-Aguiar, Alexandra G; Dillhoff, Mary; Beal, Eliza; Poultsides, George; Makris, Eleftherios; Rocha, Flavio; Crown, Angelena; Idrees, Kamran; Marincola Smith, Paula; Nathan, Hari; Beems, Megan; et al. (JAMA surgery, 2019)
Little information is available regarding the minimum number of lymph nodes needed to accurately stage patients when performing a mesenteric lymphadenectomy for small-bowel neuroendocrine tumors. To determine the prognostic role of lymph node positivity and the ideal number of lymph nodes for accurately staging patients with small-bowel neuroendocrine tumors. This case series from the US Neuroendocrine Tumor Study Group, a collaboration among 8 US-based, academic tertiary care referral centers, obtained demographic, perioperative, and pathologic data from the group's database, Social Security Death Index, and publicly available obituaries. All patients in these institutions with small-bowel neuroendocrine tumors who underwent curative-intent surgical resection of a primary tumor between January 1, 2000, and December 31, 2015, were included (n = 199). Patients with duodenal or ampullary tumors, other nonneuroendocrine concurrent malignant neoplasms, mortality of fewer than 30 days after the surgical procedure, and distant metastatic disease were excluded. Data analysis was conducted from September 1, 2017, to December 1, 2017. Primary study outcome was recurrence-free survival. Hypothesis was generated after data collection and data entry into the US Neuroendocrine Tumor Study Group database. Of the 199 patients included, 112 (56.3%) were male and 87 (43.7%) female with a mean (SD) age of 60.3 (12.5) years and a mean (SD) body mass index of 29.5 (6.0). One hundred fifty-four patients (77.4%) had lymph node-positive disease. No difference in 3-year recurrence-free survival was found between patients with lymph node-positive and lymph node-negative disease. Patients with 4 positive lymph nodes had a worse 3-year recurrence-free survival compared with those with 1 to 3 or 0 positive lymph nodes (81.6% vs 91.4% vs 92.1%; P = .01). When examining patients with fewer than 8 resected lymph nodes, no difference in 3-year recurrence-free survival was observed among patients with 4 or more, 1 to 3, or 0 positive lymph nodes (100% vs 93.8% vs 91.7%; P = .87). Retrieval of 8 or more lymph nodes, however, accurately discriminated patients with 4 or more, 1 to 3, or 0 positive lymph nodes (3-year recurrence-free survival: 79.9% vs 89.6% vs 92.9%; P = .05). The findings from this study suggest that, for patients undergoing curative-intent resection of small-bowel neuroendocrine tumors, accurate lymph node staging requires a minimum of 8 lymph nodes for examination, and 4 or more positive lymph nodes are associated with decreased 3-year recurrence-free survival compared with 1 to 3 or 0 positive lymph nodes; a thorough regional lymphadenectomy may be critical for accurate staging and management of this disease.